A review on microbe–mineral transformations and their impact on plant growth - Pradhan, Nikita; Singh, Shikha; Saxena, Garima; Pradhan, Nischal; Koul, Monika; Kharkwal, Amit C.; Sayyed, Riyaz (Frontiers in Microbiology, 2025)
Mineral–microbe interaction is a driving environmental changes, regulating the biogeochemical cycling of elements, and contributing to the formation of ore deposits. Microorganisms are fundamental to mineral transformation processes, exerting a profound influence on biogeochemical cycles and the bioavailability of critical nutrients required for plant growth. In this review, we delve into the various mechanisms by which microbes facilitate mineral dissolution, precipitation, and transformation, with a particular focus on how these processes regulate the availability of both macronutrients and micronutrients in soils. Essential microbial activities such as phosphate solubilization, iron chelation, and sulfur oxidation play a pivotal role in enhancing nutrient uptake in plants, thereby supporting sustainable agricultural practices and reducing dependence on chemical fertilizers. Furthermore, microbial-driven mineral transformations are vital for environmental remediation efforts, as they contribute to the immobilization of toxic metals and the detoxification of contaminated soils. By examining key microbial–mineral interactions—including nitrogen fixation, siderophore production, and metal precipitation—this review underscores the indispensable role of microorganisms in improving soil fertility, fostering plant growth, and bolstering ecosystem resilience. The exploration of these microbial processes reveals significant potential for advancing bioremediation strategies and the development of biofertilizers, offering promising solutions to enhance agricultural productivity and address environmental challenges.